Form follows motion: Designing public space derived from the understanding of pedestrian movement - Forsman, Teresia Maria Louise (My University, 2021)
55% of the world’s population live in urban areas today. By 2050, that number is expected to be 68% (United Nations, 2018a). The terms and conditions of our cities are rapidly changing, and more and more people inhabit streets and public spaces. At the same time, the more cars continue to fill up our streets (Trafikanalys, 2019, p. 2), the more focused our politicians and traffic planners have become on making room for even more cars (Gehl, 2010a, p. 91). There is a global will to become more sustainable and fossil free, but a reluctance to leave the car and the infrastructure that comes with it behind. The consensus is that we need to build for pedestrians, but often the actions taken to improve pedestrian life lack the deep understanding of their behaviors. There is a disconnect between the knowledge that we possess through research and the professions that are trying to make reality of it. The purpose of this master’s thesis is to support architects and planners in making the right choices; to help them understand the complexities of pedestrians in our cities and how to proactively design for them. The starting point is to develop an understanding of the pedestrian movements in our cities by uncovering the choices and behaviors that lie behind them, and to then develop strategies on how to design pedestrian-friendly public spaces, derived from that knowledge. By generating a set of design factors to assess the degree of pedestrian presence and quality of experience that a design provides or will provide, prior to its implementation, the aim is to enhance the practical skills of architects and planners in all stages of urban planning, further bridging the gap between research and practice. The chosen method for this master’s thesis was mainly research for design. The design factors were developed based on existing research and knowledge in different fields related to pedestrian movement, considering behaviors and preferences of pedestrians. The project site of Korsvägen was chosen as the design project to test the design factors, based on it being a public space handling a lot of pedestrian movement at the same time as offering room to design. It was also chosen based on its relevance due to its ongoing development plans; Gothenburg’s major infrastructure project “Västlänken”.
Keywords: Built environment studies, cities for people, human scale, human dimension, mobility, pedestrian behavior; pedestrian freedom, pedestrian movement, pedestrianism, public life studies, space syntax studies, urban public space, walkability